ScenarIoT: support for scenario specification of internet of things-based software systems - Silva, Valéria Martins da (2019)
Internet of Things (IoT) is a paradigm that allows composing systems from objects equipped with identification, sensing or acting behaviors in addition to processing capabilities, which can communicate and cooperate to achieve objectives. Similar to every paradigm shift, IoT brings up challenges related to several areas of research, including Software Engineering at different stages of development. This dissertation proposes the ScenarIoT approach aiming to support specification of scenarios in the development of software systems that are based on the Internet of Things (IoT) background. This approach is grounded on Interaction Arrangements which represent recurrent flows of interaction between abstract elements of the IoT domain. These arrangements could be designed by applying an evidence-based approach, i.e., considering the results obtained through a structured literature review conducted with the objective of identifying, analyzing and interpreting the concepts and properties of the IoT domain. The ScenarIoT approach was applied in two projects of undergraduate classes in order to observe its usefulness. The results of the studies showed that the approach is useful considering the context in which it was applied.